2018
DOI: 10.1176/appi.ps.201700250
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Risk-Based Firearm Seizure Laws in Connecticut and Indiana on Suicide Rates, 1981–2015

Abstract: Risk-based firearm seizure laws were associated with reduced population-level firearm suicide rates, and evidence for a replacement effect was mixed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 25 publications
3
84
0
Order By: Relevance
“…These programs enable law enforcement, health professionals, and families to intervene when individuals are dangerous to themselves or others. ERPOs or GVROs were associated with 7.5% reduction of firearm suicide rate in Indiana, and a 14% reduction in Connecticut [125].…”
Section: Identifying the Most Effective Firearm Safety Measuresmentioning
confidence: 96%
See 1 more Smart Citation
“…These programs enable law enforcement, health professionals, and families to intervene when individuals are dangerous to themselves or others. ERPOs or GVROs were associated with 7.5% reduction of firearm suicide rate in Indiana, and a 14% reduction in Connecticut [125].…”
Section: Identifying the Most Effective Firearm Safety Measuresmentioning
confidence: 96%
“…Increased presence of gun shops is associated with higher suicide rates, underscoring the need for more lethal means safety programs of this nature [48]. These are all very positive steps in the right direction with demonstrated efficacy in reducing suicide deaths [114,125,130], and thus the importance of these measures for improving public health cannot be overstated.…”
Section: Identifying the Most Effective Firearm Safety Measuresmentioning
confidence: 99%
“…Results to date on the effectiveness of the related risk warrant policies have been encouraging (Kivisto & Phalen, ; Swanson et al., ). Swanson and colleagues studying the effects of Connecticut's law (Swanson et al., ) estimated that one suicide is prevented for every 10 to 20 orders served—a high level of effectiveness for such an outcome.…”
Section: Gun Violence Restraining Ordersmentioning
confidence: 99%
“…''Red flag'' laws allow families to petition the court to temporarily confiscate the weapons of someone demonstrating dangerous behavior. Studies have demonstrated their effectiveness in reducing firearm suicides (Kivisto and Phalen, 2018). We often learn, after the fact, that the people closest to the perpetrator had important information about concerning behaviors that they did not share with authorities.…”
Section: Direct Threatsmentioning
confidence: 99%